Towards a National Language in Nigeria: Problems & Prospects. - Akinwale, Timothy Olayiwola (Obafemi Awolowo University, 2018)
This work sets out to find out why the issue of a choice of a national language for Nigeria has remained elusive for so long. This state of affairs has been brought about largely by the fact that the country suffers from an extreme form of linguistic complexity.